KEMASAN UNTUK MENINGKATKAN KUALITAS DAN PENJUALAN PRODUK - Endah Wening Budiningrum; Wahyudiyono Wahyudiyono; Purnama Andri Murdapa (HIKMAYO: JURNAL PENGABDIAN MASYARAKAT AMAYO, 2022)
According to several studies, packaging and product quality can increase product sales. Food packaging is a material used to contain or wrap food, whether in direct contact with food or not. Packaging has the benefit of protecting products from bad influences, protecting products so that they remain in good condition until they are in the hands of consumers. The attributes of quality and packaging features have a greater influence on all stages of purchasing decisions. So that packaging and food safety in this case quality plays an important role in product sales. Product sales are one of the main goals of SMEs in producing products. Efforts are needed to increase sales, one of which is through packaging and labeling. A good packaging method that can maintain product quality until it reaches consumers is one of the efforts to help mothers increase their product sales. PKK from Gancahan, Sidomulo Village, Godean District, Sleman Regency, DIY, are trying to increase their income by marketing their products. In this marketing effort, good packaging and labeling are needed for product packaging. Based on the above reasons, community service activities were carried out with the aim of training PKK Dusun Gancahan mothers through packaging, labeling, in the hope of increasing product sales for PKK Dusun Gancahan, Sidomulyo, Godean, Sleman DIY. The result of this community service is the ability of mothers to make economical packaging from plastic materials to wrap their processed products.